2018
DOI: 10.1016/j.clgc.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Increased Utilization of Positron Emission Tomography/Computed Tomography (PET/CT) Imaging and Its Economic Impact for Patients Diagnosed With Bladder Cancer

Abstract: We identified rapid adoption of PET/CT imaging independent of clinical stage, resulting in excess national spending of $11.6 million for this imaging modality alone. Further value-based research discerning the clinical versus economic benefits of advanced imaging among patients with bladder cancer are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The radiotracer is injected approximately 60 min prior to the scan, and the patients are instructed to follow a specific diet and activity regimen prior to the exam to avoid muscle activity and alterations in radiotracer biodistribution due to endogenous insulin release. A review of the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2011 demonstrated that a total of 36,855 patients underwent a PET/CT scan for bladder cancer of any stage and that the number of scans markedly increased throughout the time period, resulting in excess national spending of $11.6 million for this imaging modality [46,47]. However, for patients with bladder cancer, FDG-PET/CT has the potential to change patient management, and patients with positive FDG-PET/CT scans demonstrate worse overall survival and higher recurrence rates in cases of recurrent disease [48].…”
Section: Why Pet/ct For Bladder Cancer?mentioning
confidence: 99%
“…The radiotracer is injected approximately 60 min prior to the scan, and the patients are instructed to follow a specific diet and activity regimen prior to the exam to avoid muscle activity and alterations in radiotracer biodistribution due to endogenous insulin release. A review of the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2011 demonstrated that a total of 36,855 patients underwent a PET/CT scan for bladder cancer of any stage and that the number of scans markedly increased throughout the time period, resulting in excess national spending of $11.6 million for this imaging modality [46,47]. However, for patients with bladder cancer, FDG-PET/CT has the potential to change patient management, and patients with positive FDG-PET/CT scans demonstrate worse overall survival and higher recurrence rates in cases of recurrent disease [48].…”
Section: Why Pet/ct For Bladder Cancer?mentioning
confidence: 99%
“…In conclusion, the current literature suggests that 18F-FDG PET/CT provides an incremental value for nodal and distant staging in MIBC at initial diagnosis. However, due to its significant cost for healthcare systems ( 34 ), prospective studies with high evidence level are still needed before its use can be formally adopted into consensus guidelines and recommendations ( 3 , 18 , 35 , 36 ). In support of its role in distant staging, a recent consensus statement revealed that 18F-FDG PET/CT is the imaging modality of choice to avoid over-treatment in oligometastatic patients with an agreement of 88% of participants ( 37 ) ( Figure 1B ).…”
Section: Risk Stratification At Diagnosismentioning
confidence: 99%
“…However, use of F-18 FDG PET/CT in urinary system has developed slowly due to the uptake of F-18 FDG in urine. Though previous studies showed that delayed diuretic PET/CT could be used in the diagnosis of bladder cancer (12)(13)(14), only few studies investigated the value of F-18 FDG PET/CT in upper urinary tract-occupying lesions. Though the diagnostic sensitivity of F-18 FDG PET/CT for detecting metastasis was superior to CT in upper urinary tract carcinoma, it was not feasible to detect the primary tumor because of the radiotracer in the urine (15).…”
Section: Introductionmentioning
confidence: 99%